Synergistic Effect of Diallyl Sulfide With Zinc Oxide Nanorods: A Novel and Effective Approach for Treatment of Acute Dermatitis in Model Animals - Rauf, Mohd A.; Zubair, Swaleha; Ateeq, Hira; Dabeer, Khadija; Pachauri, Subodh; Ajmal, Mohd; Owais, Mohammad (Frontiers in Microbiology, 2018)
Besides inciting persistent and recurrent nosocomial afflictions, Staphylococcus aureus (S. aureus), a biofilm forming pathogen, poses an increased risk of several skin as well as respiratory tract infections as well. Emerging antimicrobial resistance trend asks to search for better alternate non-antibiotic options to combat S.aureus pathogen. In the present study, we evaluated the synergistic antimicrobial potential of Zinc oxide nanorods (ZnO-NRs) and Diallyl sulphide (DAS) emulsion against methicillin-resistant Staphylococcus aureus (MRSA). The antimicrobial assessment study suggests that the ZnO-NR and DAS emulsion effectively suppressed both sensitive S. aureus as well as MRSA isolates. The combination treatment showed enhanced activity even at a lower concentration as compared to the single treatment of ZnO-NRs and DAS emulsion alone. The ZnO-NRs-DAS showed significant inhibition of MRSA biofilm as well. The combined ZnO-NRs-DAS emulsion therapy successfully treated experimental topical dermatitis infection caused by MRSA in mice model.